Efficacy and safety of erlotinib combined with bevacizumab in the treatment of non-small cell lung cancer: A systematic review and meta-analysis - Zhou, Kenan (Medicine (Baltimore), 2020)
BACKGROUND: Non-small cell lung cancer (NSCLC) has a poor prognosis despite conventional treatments of surgery, radiotherapy, and chemotherapy. Small-molecule tyrosine kinase inhibitors acting on epidermal growth factor receptor (EGFR) have shown high efficacy and low toxicity for NSCLC. In particular, combining erlotinib with the VEGF antibody bevacizumab has therapeutic value in NSCLC, but the drugs’ separate effects as monotherapy and any adverse outcomes of combination therapy remain unclear. OBJECTIVES: To determine the efficacy and safety of erlotinib and bevacizumab for NSCLC, we conducted a meta-analysis and systematic review of randomized controlled trials. DATA SOURCES: PubMed, Embase, Web of Science, and Cochrane databases were searched using keywords and manual review. STUDY ELIGIBILITY CRITERIA, PARTICIPANTS, AND INTERVENTIONS: We reviewed randomized controlled trials on the use of erlotinib combined with bevacizumab in adult patients with NSCLC, including data on outcome measures of overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and adverse events. STUDY APPRAISAL AND SYNTHESIS METHODS: After quality assessment, datasets were evaluated for heterogeneity. In the event of significant heterogeneity, a random-effects model was used to assess the overall outcome measures as a result of treatments. Subgroup analysis was conducted to evaluate the source of heterogeneity on PFS. RESULTS: Compared with erlotinib or bevacizumab alone, the combined treatment did not significantly prolong OS (95% confidence interval [CI] = 0.84–1.11; P = .62) or increase the ORR (95% CI = 0.91–1.20; P = .52), but significantly improved PFS (95% CI = 0.58–0.73; P < .001). This improvement was especially notable in patients with the following characteristics: Eastern Cooperative Oncology Group Performance Status score of 0 or 1, female, no smoking history, adenocarcinoma, and EGFR Exon19 deletion or Exon21 Leu858Arg mutation. Combination therapy significantly increased incidence of grade 1–2 hypertension (20.3% vs 6.3%, 95% CI 1.73–5.88; P < .01) and severe diarrhea (10% vs 3.2%, 95% CI 1.36–6.60; P = .01). LIMITATIONS: The low number of available randomized controlled trials could influence interpretation. CONCLUSIONS: Compared with erlotinib or bevacizumab monotherapy, their combination effectively prolongs PFS but increases incidence of adverse events in NSCLC patients.